Implementasi Perjanjian Mutual Legal Assistance Dalam Rangka Pengembalian Hasil Kejahatan di Luar Negeri - Mochammad Abizar Yusro; Thufail Rozaan (Nagari Law Review, 2020)
The development of science, technology and information, does not always have a positive impact, on the other hand these developments have a negative impact, such as the development of criminal acts from the conventional nature to organized and transnational crime (organized and transnational crimes). Preventing and eradicating organized and transnational criminal acts is not carried out in conventional ways, such as catching the perpetrators of criminal acts (follow the suspect), this method is not effective to do because to prove the existence of criminal acts against organized and transnational criminal acts is very difficult. Efforts to return the stolen asset recovery (stolen asset recovery) through corrupt acts tend not to be easy. The perpetrators of corruption have extraordinarily broad and difficult to reach access to conceal or carry out money laundering resulting from corrupt acts by utilizing derivative transactions through effective international transfers. The problem becomes even more difficult because the safe haven for the proceeds of crime goes beyond national borders. Therefore, through the concept of stolen asset recovery which is integrated with mutual legal assistance, it is able to become a solution to restore state assets abroad. This research is descriptive in nature with normative juridical research type. The type of approach used is the statutory approach and conceptual approach.